2016
DOI: 10.3390/nu8050266
|View full text |Cite
|
Sign up to set email alerts
|

Sun Exposure Guidelines and Serum Vitamin D Status in Denmark: The StatusD Study

Abstract: Little is known on how vitamin D status is affected by adherence to UVB-limiting sun exposure guidelines. Our aim was to investigate the relationship between adherence to the Danish sun exposure guidelines and vitamin D status. In total, 3194 Danes (2625 adults, 569 children) were recruited among the general population, and more than 92% had blood samples taken both autumn and spring. Using linear regression, we associated serum vitamin D concentrations to questionnaire responses on: seeking shade, wearing a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…sufficient UVR exposure to reach sufficient levels of Vitamin D, an area where different opinions remain [5,53,54]. …”
Section: Discussionmentioning
confidence: 99%
“…sufficient UVR exposure to reach sufficient levels of Vitamin D, an area where different opinions remain [5,53,54]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent sunbed use was shown to increase risk of skin cancer compared to non‐recent use . The model did not include any potential positive health effects of commercial sunbed use, because there was considered to be none, like, for example, from vitamin D–related illness as vitamin D is not a general problem in the population group affected by the discussed interventions . In addition, any vitamin D supplementation needed in subgroups is available from non‐harmful sources.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also show that the use of sunscreen with SPF >15 had no effect on serum 25(OH)D levels during summer months in children with AD, in agreement with the results of a Danish study that reported adequate VD status in children that used sunscreen. 36 It has been shown that the usual application of 0.8-1 mg/cm 2 of sunscreen is less than the recommended amount of 2 mg/cm 2 and that pre-vitamin D can be formed when lower amounts of SPF ≤30 sunscreen are applied due to penetration of the skin by significant amounts of UV radiation. 37…”
Section: Ad N (%) Controls N (%) P-valuementioning
confidence: 99%